Anti-prothrombin antibodies as a potential risk factor of recurrent venous thromboembolism - Zanon, Ezio; Saggiorato, Graziella; Ramon, Roberto; Girolami, Antonio; Pagnan, Antonio; Prandoni, Paolo (Thrombosis and Haemostasis, 2004)
The role of antiprothrombin (aPT) antibodies in the development of venous thromboembolism (VTE) is still uncertain. The aim of this study was to evaluate the potential role of aPT antibodies in the development of recurrent thromboembolism. Out of 236 consecutive symptomatic patients with an episode of acute VTE, antiphospholipid antibodies were found in 85 (36.0%), of whom 24 were carriers of aPT antibodies (10.2% of the entire cohort). A history of previous thromboembolism was identified in 56 patients (23.7%). The prevalence of previous thromboembolism was significantly higher in carriers than in non-carriers of antiphospholipid antibodies (OR=2.4; 95% CI, 1.3 to 4.4). Of the 24 patients with aPT antibodies, 12 had a history of previous thromboembolism. In a multivariate logistic regression analysis, in which the other categories of antiphospholipid antibodies were taken into account, as well as the patient’s age, sex, and the modality of clinical presentation, it was found that the presence of aPT antibodies was significantly associated with the prevalence of prior thromboembolism (OR=3.3; 95% CI, 1.3 to 8.6). Since aPT antibodies are more commonly identifiable in patients with multiple thrombotic episodes, they are a likely risk factor for recurrent thromboembolism.
Keywords: Anti-phospholipid antibodies; anti-prothrombin antibodies; venous thromboembolism